Pendampingan Masyarakat Dalam Pengelolaan Kopi Robusta di Indrokilo - Erna Wijayanti; Jeshica Ayu Rachmawati; Titik Rahmawati; Ira Nailas Sa'adah (LP2M of Institute for Research and Community Services - UIN Walisongo, 2020)
Coffee is one of the main potentials of Indrokilo Hamlet, Lerep Village, West Ungaran District. The abundance of the coffee harvest in this region has not been matched by the community's ability to process resources optimally. This service program aimed to provide assistance and training in coffee management according to the standards so that the quality of Indrokilo Robusta Coffee can be optimized. The subjects of this study were the community of Dusun Indrokilo who were the members of the Kelompok Wanita Tani (KWT), community shops, and youth groups. The companion partners in this research are the Community Empowerment Team of Djarum Scholarship Plus and the Komunitas Tangan Di Atas (TDA). The techniques used in this mentoring are in the form of training and coffee processing practices followed by monitoring and evaluation of the end of the activity. The results of this assistance made the community more aware of the importance of Quality Control of coffee; the importance of product marketing through E-Commerce; construction of a special drying house for coffee, sorting practices, storage and drying of coffee beans; assistance and training procedures for processing and packaging of coffee products according to standards. Kopi merupakan salah satu potensi utama Dusun Indrokilo, Desa Lerep, Kecamatan Ungaran Barat. Melimpahnya hasil panen kopi di wilayah ini belum diimbangi dengan kemampuan masyarakat untuk mengolah sumber daya dengan optimal. Program pengabdian ini bertujuan untuk memberikan pendampingan dan pelatihan pengelolaan kopi sesuai standar agar kualitas dan harga jual Kopi Robusta Indrokilo dapat dioptimalkan. Subjek penelitian ini adalah masyarakat Dusun Indrokilo yang tergabung dalam Kelompok Wanita Tani (KWT), tokoh masyarakat, dan kelompok pemuda. Mitra pendamping dalam penelitian ini yaitu Tim Community Empowerment Djarum Beasiswa Plus dan Komunitas Tangan Di Atas (TDA). Teknik yang digunakan dalam pendampingan ini berbentuk pelatihan dan praktek pengolahan kopi yang dilanjutkan dengan monitoring dan evaluasi akhir kegiatan. Hasil dari pendampingan ini membuat masyarakat semakin sadar akan pentingnya Quality Control kopi; pentingnya pemasaran produk melalui E-Commerce; serta pembangunan rumah jemur khusus kopi dan praktek sortasi, penyimpanan dan penjemuran biji kopi; tata cara pengolahan dan pengemasan produk kopi sesuai standar.